Feasibility Analysis Of Rsa Algorithm In Security Of Lecturer Performance Data - Muhammad Fikry; Bustami (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
Lecturer performance data is an important data that must be possessed by every lecturer and institution, therefore efforts are needed to ensure quality management of the university. For this reason, it is necessary to get the right algorithm to secure data. The RSA (Rivest- hamir-Adleman) algorithm is one of the public key algorithms in the field of cryptography which is popular and widely used today. The number one factor that can be used to carry out prime numbers is a long time to do the factoring. Data that is encrypted with the RSA algorithm must be changed to universal code, namely ASCII (American Standard Code for Information Interchange) or the American Standard Code for nformation exchange are the International Standard in universal letters and symbol codes. Based on the Basic Tri Dharma of Higher Education, measurement of lecturer performance needs to be carried out in accordance with their original objectives. Data can be obtained from each lecturer up to date with good data security.